Assessment of climate adaptation options for cereal-based systems in the eastern Indo-Gangetic Plains, South Asia - CGIAR Research Program on Maize (2019)
All the crop management options studied increased yield, water productivity and net returns over that of the Current farmers Ppractice, under the current and future climate scenarios. However, the partial crop residue retention treatment gave significantly higher relative yield, lower annual yield variability and a higher benefit-cost-ratio than the other treatments across cropping system components and climate periods.